PENGEMBANGAN FLASHCARD “SPOKEN” UNTUK MENINGKATKAN KETERAMPILAN MENULIS KALIMAT AKTIF SISWA KELAS II SEKOLAH DASAR - Agwianndini, Grace; Septian Airlanda, Gamaliel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The habit of communicating with English in daily life causes a decrease in students' ability to speak Indonesian. This research aims to develop Flashcard